Design substantiation of the three-tier centrifugal type mineral fertilizers spreader. - Kobets, A. S.; Кобець, Анатолій Степанович; Naumenko, M. M.; Науменко, Микола Миколайович; Ponomarenko, N. O.; Пономаренко, Наталія Олександрівна; Kharytonov, M. M.; Харитонов, Микола Миколайович; Velychko, O. P.; Величко, Олександр Петрович; Yaropud, V. M.; Яропуд, Віталій Миколайович; et al. (INMA BUCHAREST, 2017)
The mathematical model for substantiation of engineering factors of machineries for centrifugal type mineral fertilization is developed. It is proposed the design of the disk application for which one could improve evenness of mineral fertilizers spreading by centrifugal type spreaders. Simplified formulas for agricultural engineering usage, givingthe opportunity to explain the construction of the fertilizer spreader which provides qualitative spreading for the given bandwidth, are also presented. Розроблено математичну модель для обґрунтування технологічних параметрів машин для внесення мінеральних добрив відцентрового типу. Запропонована конструкція диска, застосування якого може покращити рівномірність розсівання добрив розкидачами відцентрового типу. Виведені спрощені для інженерного застосування формули, що дають можливість обґрунтовувати конструкцію дискового розкидача добрив, який забезпечує якісне розсівання на смугу заданої ширини.
Обгрунтування дизайну три рівневого відцентрового розкидача мінеральних добрив
Keywords: fertilizer; добриво; centrifugal spreader; розкидувач відцентровий; disk distribution quality; якість розподілу диску; movement analysis; аналіз руху; spreading features; особливості розсіювання